Filicide: the Australian story. (December 2020) - Brown, Thea; Tyson, Danielle; Fernandez Arias, Paula
Abstract: A filicide death, meaning the killing of a child by their parent or equivalent guardian, is a tragic event. Sadly, a UK study suggests Australia has the fourth highest rate of filicide among similar developed nations. Since Australian research studies on the incidence of filicide, or indeed on any other aspect of the problem, are limited, it is impossible to know if this finding is correct or not. However, in the last several years more research on filicide has emerged in Australia and by reviewing the recent research in detail, this article develops an integrated analysis of Australian filicide research and contributes to the knowledge bank on Australian filicide that can be used by professionals undertaking practice and research in intervention and prevention. Analysis of the studies shows one child dies at the hands of a parent every fortnight and that this number has not changed for many years. The analysis identifies the profiles of victims and perpetrators. The constellation of circumstances and stressors associated with each of the parental perpetrator groups is discussed, including the perpetrators' contact with, and mostly unsuccessful use of, services. Based on the analysis, a way forward to prevention is proposed.